Pelatihan Pengelolaan Keuangan Rumah Tangga dalam Rangka Peningkatan Kesejahteraan Keluarga - Tangke, Diar Muzna; Andriany, Dynne; Latuamury, Sherlie Evabiony; Talaohu, Malampati (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Family economic problems start from a lack of knowledge about household financial management. This activity aims to provide knowledge about household financial management for housewives so that they can meet the family's current and future needs appropriately so as to create a prosperous family. The method of this activity is to provide training to participants directly and there is a pre-test and post-test to determine participants' understanding before and after the training activity. The results of this activity provide knowledge to housewives as financial managers. This can be seen from the post-test score regarding household financial management which is greater than the pre-test before the training and active discussion sessions from the participants. Apart from that, this activity provides awareness for participants to be able to recognize financial conditions so that they can use their income effectively and efficiently to meet family needs.